Analisis Cemaran Kapang dan Khamir pada Jamu Serbuk Instan Jahe Merah dan Temulawak - Dion, Romario; Purwantisari, Susiana (Berkala Bioteknologi, 2020)
ABSTRACTInstant herbal medicine is a powder or granule form of herbal medicine that is usually made from sugar and spices which are combined with or without the addition of other food ingredients and food additives. Powdered herbal medicine has the advantage that it is practical and fast in serving, and has a relatively long shelf life. However, poor processing of herbal powder can lead to microbial contamination such as mold and yeast. This study aims to determine the presence of mold and yeast contamination contained in the red ginger and ginger powder herbs. The steps taken in this study were sampling, preparation of tools and materials, homogenization and sample dilution, and testing for mold and yeast levels. This research was conducted for 2 months from August to September 2020 at the Biotechnology Laboratory, Department of Biology, Faculty of Science and Mathematics, Diponegoro University. The results showed that the mold and yeast levels found in the red ginger powder herbal sample were 1 x 101 colonies / g, while the mold and yeast levels found in the ginger powder herbal medicine were 21 x 101 colonies / g. of the two samples have met the standards of BPOM RI Regulation Number 32 of 2019 so that it can be concluded that the red ginger and ginger powder herbs are still safe for consumption.Keyword :  Herbal powder, Contaminants, Molds and Yeasts